BEYOND CODE: A COMPREHENSIVE FRAMEWORK FOR ENHANCING SOFTWARE ENGINEERING PROFICIENCY IN MODERN DEVELOPMENT ENVIRONMENTS - Revanth Pathuri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
In the rapidly evolving field of software engineering, technical proficiency alone is no longer sufficient for creating robust, scalable, and maintainable systems. This article presents a comprehensive framework for enhancing software engineering skills beyond coding, focusing on five critical areas: strategic tool selection, avoiding over-engineering, judicious use of caching, logical system separation, and comprehensive testing strategies. Through a systematic review of current industry practices and academic literature, supplemented by case studies from leading tech companies, we identify key principles and best practices in each area. Our findings reveal that effective decision-making in these domains significantly impacts system performance, maintainability, and overall project success. The article demonstrates that engineers who master these strategic principles are better equipped to design and implement complex systems that meet both immediate requirements and long-term scalability needs. This article contributes to the growing body of knowledge on holistic software engineering practices and provides practical guidelines for both individual engineers and organizations seeking to improve their software development processes.